Partitioning of Dry Matter in Relation to Yield Performance in Five Cultivars of Cowpea, Vigna unguiculata s. sp. unguiculata - Alofe, C. O.; Amusan, A. A. (Faculty of Agriculture, University of Ife, 2015)
Dry matter accumulation (DMA) and its pattern of partitioning were studied in five cultivars of cowpea, Vigna unguiculata ssp. Unguiculata (L.) Walp. Generally, TVx 183P9G and TVx 1193-9F flowered and podded earliest while TVu 1190E and Tvu 1977 were the slowest to flower and pod; Ife Brown was intermediate. TVu 1977 and TVu 1190E accumulated more dry matter in their stems, leaves and pods than any of the other cultivars. The proportion of dry matter deployed into pods was highest in TVx 1836-9G (81 percent) and TVx 1193-9F (75 percent), and least in TVu 1190E and TVu 1977 (63 and 67 percent each). In Ife Brown, it was 67 percent. Grain yields were similar in TVu 1977, TVu 1190E and TVx 1836-9G (505, 528 and 516 kgha respectively), but only 3 59 kgha in Ife Brown. I t was 472 kgha in TVx 1193-9F. Harvest index was low in TVu 1190E and TVu 1977 (18 and 20 percent, respectively), medium in Ife Brown (23 percent) and high in TVx 1836-9G and TVx 1193-9F (30 and 26 percent respectively). Correlation between seed yield and DMA though positive, was not significant. No correlation was observed between seed yield and harvest index, but correlation between DMA and harvest index was negative and significant.